Mainstreamed genetic testing in ovarian cancer: patient experience of the testing process. Issue 2 (19th November 2019) - McLeavy, Laura; Rahman, Belinda; Kristeleit, Rebecca; Ledermann, Jonathan; Lockley, Michelle; McCormack, Mary; Mould, Tim; Side, Lucy; Lanceley, Anne
Abstract : Objective: Pathogenic BRCA variants account for 5.8–24.8% of ovarian cancers. The identification of such a variant can have a significant impact on the affected individual and their relatives, determining eligibility for targeted therapies, predicting treatment response, and granting access to disease prevention strategies. Cancer services are responding to the increased demand for genetic testing with the introduction of mainstreamed genetic testing via oncology clinics. This study aimed to evaluate patient experience of the mainstreamed genetic testing pathway at a tertiary referral center in London, UK. Methods: Study participants were patients diagnosed with high-grade non-mucinous ovarian cancer, tested via a mainstreamed genetic testing pathway at the tertiary referral center between February 2015 and June 2017. Eligible participants were invited to complete the retrospective study questionnaire. Five quantitative measures with additional free-text items were used to evaluate the patient experience of mainstreamed genetic testing. Results: The tertiary referral center tested 170 ovarian cancer patients. Twenty-three pathogenic BRCA mutations were identified (23/170, 13.5%). One-hundred and six patients (106/170, 62.4%) met the study inclusion criteria. Twenty-nine of those invited to participate (29/106, 27.4%) returned the retrospective study questionnaire. Pathogenic BRCA1/2 variants were identified within four respondents (4/29, 13.8%). Motivations for genetic testing related to improved medical management, and the ability to provide relatives with genetic information. Participants did not appear to be adversely affected by result disclosure post-mainstreamed genetic testing. Two individuals with a pathogenic variant reported that the support provided by the tertiary referral center post-result disclosure could have been improved. Conclusion: Results of the current study support further psychosocial research into the expansion of the mainstreamed genetic testing pathway. The results, although promising, have also highlighted the importance of genetic awareness within the multi-disciplinary team and the provision of timely psychological support from genetic specialists.